2006
DOI: 10.3201/eid1204.050602
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Lyme Disease

Abstract: Since 1975, Lyme disease has become the most common vectorborne inflammatory disease in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 17 publications
3
65
0
Order By: Relevance
“…Our study confirms and extends results of the 1993 survey by Vanderhoof and Vanderhoof-Forschner, in which 19% of patients with Lyme disease reported that they had lost a job due to the illness [21], and is consistent with those of Zhang and colleagues, who found that loss of productivity -such as lost work time -constituted over half of the costs associated with late Lyme disease [28]. The economic burden for patients and society may be exacerbated as a result of several factors, including delayed diagnosis that permits an acute condition to become chronic, the inability to obtain medical insurance when Lyme disease is a pre-existing condition, and denial of disability benefits to patients who are unable to work.…”
Section: Burden Of Illnesssupporting
confidence: 91%
See 2 more Smart Citations
“…Our study confirms and extends results of the 1993 survey by Vanderhoof and Vanderhoof-Forschner, in which 19% of patients with Lyme disease reported that they had lost a job due to the illness [21], and is consistent with those of Zhang and colleagues, who found that loss of productivity -such as lost work time -constituted over half of the costs associated with late Lyme disease [28]. The economic burden for patients and society may be exacerbated as a result of several factors, including delayed diagnosis that permits an acute condition to become chronic, the inability to obtain medical insurance when Lyme disease is a pre-existing condition, and denial of disability benefits to patients who are unable to work.…”
Section: Burden Of Illnesssupporting
confidence: 91%
“…Although IDSA discounts the severity of Lyme disease symptoms, the utilization of hospital and emergency room services by respondents suggests a substantial burden of illness. This corroborates previous reports that patients with Lyme disease suffer a disability equal to that of congestive heart failure [25,35] and that hospital and emergency room services constitute a large component of direct medical costs in Lyme disease [28]. In addition, a quarter of survey respondents received disability benefits at some point in their illness, and over half of these respondents received disability for two years or more, indicating significantly compromised ability to function in their work capacities.…”
Section: Burden Of Illnesssupporting
confidence: 88%
See 1 more Smart Citation
“…CRE infections are more costly than episodes of other infectious diseases. For example, in 2016 values, the cost of one influenza case is an estimated $2807 to $8889 to society [22]; the societal costs of pertussis in adolescents and adults is an estimated $600 to $1169 [23]; Lyme disease cost societyan estimated $451 per case [24]; and food-borne illness because of salmonella cost society $3899 per case [25]. CRE infections are also more costly compared with the annual costs of some chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Lyme borreliosis has large socioeconomic consequences. Studies from different countries show that maximum estimated costs per patient approach e9000, including direct and indirect costs (Maes et al 1998, Meltzer et al 1999, Zhang et al 2006, Henningsson et al 2010, Morlando et al 2012.…”
Section: Introductionmentioning
confidence: 99%